Senam Otak dapat Meningkatkan Fungsi Kognitif Lansia Penderita Demensia - Khairil Umam; Bambang Suryadi; Wesli Daeli (Open Access Jakarta Journal of Health Sciences, 2021)
Introduction: Vulnerable population includes someone with an advanced age, an elderly person is someone who has reached 60 years of age. Objective: to determine the effect of brain exercise in the elderly on cognitive function with dementia in social institutions. Method: The research design used in this study was astudy quasi-experimental involving 15 elderly people with dementia in one of the social institutions in the Ciracas area. The instrument used was a questionnaire by comparing the pre-test and post-test results. Result: 7 (47%) elderly with moderate cognitive impairment were given before brain exercise and there were 8 (53%) elderly with mild cognitive impairment after brain exercise. The results of the Paired Sample t-test showed that there was an effect before and after giving brain exercise to elderly people with dementia (pre-test mean t = 19.73, post-test mean t = 20.87; p =0.009). Conclusion: From the results of this study, it can be concluded that there is an effect of brain exercise in the elderly on cognitive function in people with dementia.